Inhibition of Enzymes by Human Salivary Immunoglobulin A - Fukui, Yoshio (1973)
Human whole saliva inhibited bacterial neuraminidases and the inhibition was found to reside in the salivary IgA fraction. Further, salivary immunoglobulin (Ig)A inhibited various bacterial enzymes and toxins: neuraminidases from Streptococcus mitis, Streptococcus sanguis, and Clostridium perfringens, hyaluronidase and chondroitin sulfatase from oral bacteria, diphtheria toxin, and streptolysin O. The inhibitory activity of salivary IgA did not correlate with that of serum on the basis of minimum inhibitory dose. A small amount of salivary IgA was required to inhibit oral bacterial neuraminidases, whereas a large amount was required to inhibit other bacterial neuraminidase. Therefore, it is concluded that the absence of neuraminidase activity of oral bacteria in whole saliva may be due to specific inhibition by salivary IgA.